The impact of Facebook content on mental health status among Generation Z: A literature review - Yusuf, Naufal Alauddin; Astuti, Retna Tri (Universitas Muhammadiyah Magelang, 2025)
The rise of digital media has transformed how Generation Z (Gen Z) interacts, communicates, and accesses information. Though digital platforms offer benefits such as connectivity, education, and entertainment, their impact on mental health has raised concerns. Research reveals a complex relationship between digital media use and Gen Z’s mental well-being. Social media such as Facebook can provide opportunities for social support and self-expression but is also linked to anxiety, depression, cyberbullying, and self-image disorders. However, limited review study evaluates the impact of Facebook on mental health status of Gen Z population. This study evaluates the influence of Facebook on Gen Z’s mental health. A literature review was conducted using databases include Google Scholar, PubMed, and Scopus, focusing on articles published between 2020 and 2024 in English and Indonesian. Findings suggest that adolescents' use of Facebook promote self-expression and social support, but it can also trigger mental health problems. Problematic internet use is also associated with loneliness and maladaptive coping styles. Although some psychoeducation-based interventions have been conducted, there is a need for further studies to develop more specific approaches to prevent the psychological distress among Gen Z. Keywords: Community nurses, Facebook, Generation Z, innovation strategies, mental health issues